Selecting plant traits for soil erosion control in grassed waterways under a changing climate: A growth room study. (23rd October 2020) - Lees, Corina; de Baets, Sarah; Rickson, Jane; Simmons, Robert W.
Abstract: Grassed waterways are used to mitigate the offsite transport of sediment generated by soil erosion. This study used a novel trait‐based ranking approach as a method to screen potential candidate grass monocultures and mixes based on their theoretical performance in reducing (a) detachment via rainsplash, (b) detachment via scouring due to concentrated flow and (c) sediment transport and deposition processes. Selected grass species were grown under simulated UK summer and autumn establishment conditions under three different replicated rainfall scenarios: drought, normal rainfall and excess rainfall. The grass species used were the novel hybrid species Festulolium cv Prior (Fest_1) and Festulolium Bx511 (Fest_2) and a conventional mixture of Lolium perenne and Festuca rubra (Conv). Monocultures and mixtures of these species were studied. Plant traits pertinent to control of soil erosion by water were measured. Aboveground traits included plant height, percentage ground cover, aboveground biomass, stem diameter, stem area density and number of tillers. Belowground traits included total root length, root total surface area, belowground biomass, root diameter and % fine roots ≤0.25 mm. For summer conditions, the species treatments that had the highest overall soil erosion mitigation potential were Conv, Fest_1 + 2 + Conv and Fest_2. For autumn conditions, the best treatments were Fest_1 + 2, Fest_1 + 2 + Conv and Conv. The Fest 1 + 2 + Conv had more desirable traits for erosion control than mono Festulolium treatments for the autumn conditions. The conventional mixture had more desirable traits for erosion control than mono Festulolium treatments in both climate scenarios. The results indicate that the trait‐based ranking approach utilized in this study can be used to inform rapid screening of candidate grass species for soil erosion control. Highlights: How to select the most suitable grass species for soil erosion control under changing climate conditions? A novel scoring system based on plant traits associated with soil erosion mitigation was developed. Fest_1 + 2 and Conv treatments expressed traits strongly associated with maximum soil erosion mitigation. Species selection for grassed waterways should consider the establishment growing season and expected rainfall.